2015
DOI: 10.3892/mmr.2015.4430
|View full text |Cite|
|
Sign up to set email alerts
|

NADPH oxidase 3-associated oxidative stress and caspase 3-dependent apoptosis in the cochleae of D-galactose-induced aged rats

Abstract: Oxidative damage to mitochondrial DNA (mtDNA) and cell apoptosis are heavily implicated in aging. Our previous study established a mimetic rat model of aging in the cochleae using D-galactose (D-gal), and revealed that chronic injection of D-gal can increase oxidative stress and mtDNA common deletions (CD). The aim of the present study was to investigate the sources of reactive oxygen species and the occurrence of apoptosis in the cochleae of rats following 8 weeks of D-gal exposure. The results of the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
8
1
Order By: Relevance
“…Several studies indicate that loss of V-ATPase triggers apoptosis by increasing ROS. High levels of ROS result in mitochondrial membrane depolarization, release of cytochrome C and activation of apoptotic machinery that includes caspases ( Lin and Beal, 2006 ; Du et al, 2015 ; Wang et al, 2017 ). However, we observed a decrease in CellROX signals in the atp6v1f −/− mutant hair cells, indicating that elevated levels of ROS is not a cause of hair cell death in these mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that loss of V-ATPase triggers apoptosis by increasing ROS. High levels of ROS result in mitochondrial membrane depolarization, release of cytochrome C and activation of apoptotic machinery that includes caspases ( Lin and Beal, 2006 ; Du et al, 2015 ; Wang et al, 2017 ). However, we observed a decrease in CellROX signals in the atp6v1f −/− mutant hair cells, indicating that elevated levels of ROS is not a cause of hair cell death in these mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Large amounts of evidence have confirmed that chronic systemic administration of D-gal can induce aging-related changes, including the corruption of spatial learning, memory impairment, lowered antioxidant enzyme activities and increased production of ROS [30]. Therefore, chronic injection of D-gal has been demonstrated as an effective way to establish an animal model for studying cognitive disorders and aging, as well as drug testing [31]. The present study evaluated the effects of leonurine on D-gal-induced aging mice, and the results demonstrated that leonurine prevented aging.…”
Section: Discussionmentioning
confidence: 99%
“…7 A). Previous studies have linked cisplatin-induced upregulation of iNOS , NOX3 and KIM-1 to cause oxidative damage to the cochlea 47 49 . Similarly, we observed increases in these genes in the cochlea following infection with adenoviral vector expressing RGS17 .…”
Section: Resultsmentioning
confidence: 99%